The larva of Polycentropus ierapetra Malicky 1972 (Trichoptera: Polycentropodidae), including a key to the larvae of genus Polycentropus (Curtis 1835) in the Hellenic western Balkan region - Karaouzas, Ioannis; Waringer, Johann (Zootaxa, 2017)
Genus Polycentropus Curtis 1835 is represented in Greece by three species: Polycentropus excisus Klapálek 1894, P. flavomaculatus (Pictet 1834) and P. ierapetra Malicky 1972. The larvae of the former two species are well known, whereas the larva of P. ierapetra was hitherto unknown. In this paper, we describe the larva of P. ierapetra; diagnostic features of the species are listed and illustrated, and some information on its ecology is included. In addition, diagnostic characters for the larvae of the known Polycentropus species occurring in the Hellenic western Balkan region are provided.